Cell-Free Protein Synthesis From Fast-Growing Vibrio natriegens - Failmezger, Jurek; Scholz, Steffen; Blombach, Bastian; Siemann-Herzberg, Martin (Frontiers in Microbiology, 2018)
Vibrio natriegens constitutes one of the fastest-growing nonpathogenic bacteria and a potential novel workhorse for many biotechnological applications. Here, we report the development of a Vibrio-based cell-free protein synthesis system (CFPS). Specifically, up to 0.4 g L−1 eGFP could be successfully synthesized in small-scale batch reactions using cell-free extract obtained from fast-growing V. natriegens cultures. Versatile CFPS system characterization attained by combining the analyses of key metabolites for translation and ribosomes revealed limitations regarding rRNA stability and critical substrate consumption (e.g., amino acids). Alternatively, rRNA showed increased stability by inducing Mg2+ homeostasis in the reaction. Although the enormous translation capacity of the CFPS system based on the available ribosome concentration could not yet be fully exploited, its potential was successfully demonstrated by activating an endogenous transcription unit with V. natriegens RNA polymerase (RNAP) for protein expression. This allowed the use of in vitro screening for promoter strength, a critical factor for efficient gene expression in vitro and in vivo. Three different promoters were tested and output signals corresponded well with the expected affinity for V. natriegens RNAP. This established CFPS toolbox may provide a foundation to establish V. natriegens as a valuable platform in biotechnology as well as synthetic biology.